2007
DOI: 10.4310/cntp.2007.v1.n1.a1
|View full text |Cite
|
Sign up to set email alerts
|

Electric-magnetic duality and the geometric Langlands program

Abstract: The geometric Langlands program can be described in a natural way by compactifying on a Riemann surface C a twisted version of N = 4 super Yang-Mills theory in four dimensions. The key ingredients are electric-magnetic duality of gauge theory, mirror symmetry of sigma-models, branes, Wilson and 't Hooft operators, and topological field theory. Seemingly esoteric notions of the geometric Langlands program, such as Hecke eigensheaves and D-modules, arise naturally from the physics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

31
2,064
0
11

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 842 publications
(2,106 citation statements)
references
References 143 publications
(395 reference statements)
31
2,064
0
11
Order By: Relevance
“…This result agrees with the transformation for the N = 4 supersymmetries and fermions derived in [50] by other means. Also, observe that under S 2 = −½ we have ψ → iψ.…”
Section: B1 Left-moving Fermionic Zero-modesupporting
confidence: 81%
See 2 more Smart Citations
“…This result agrees with the transformation for the N = 4 supersymmetries and fermions derived in [50] by other means. Also, observe that under S 2 = −½ we have ψ → iψ.…”
Section: B1 Left-moving Fermionic Zero-modesupporting
confidence: 81%
“…Fortunately, there is an ambiguity in the SL(2, ) transformation of the fermions. As was pointed out in [50], the transformation is not unique, but rather can be combined with an automorphism of the supersymmetry algebra. The Montonen-Olive conjecture states that SL(2, ) should commute with the Poincare symmetries, but there is still the global SU (4) R symmetry.…”
Section: B1 Left-moving Fermionic Zero-modementioning
confidence: 99%
See 1 more Smart Citation
“…(3.29) of Ref. [17] which discusses the geometric Langlands program. One can show the above equations imply that the BPS configurations satisfy the field equations.…”
Section: Dyonic Monostring Websmentioning
confidence: 99%
“…This rather surprising fact is natural from the point of view of generalized complex geometry, see Hitchin (2003), and has been explained from that point of view in section 4.6 of Gualtieri (2003), as a general statement about complex symplectic manifolds. In Kapustin & Witten (2007), sections 5.2 and 11.3, it was shown that quantum geometric Langlands is naturally understood in precisely this setting.…”
mentioning
confidence: 99%